Determination of amphetamines, ketamine and their metabolites in hair with high-speed grinding and solid-phase microextraction followed by LC-MS - Liang Meng (Taylor & Francis Group, 2021)
A novel hair sample pre-treatment method based on high-speed grinding and solid-phase microextraction (SPME) had been applied for the determination of amphetamines, ketamine and their metabolites in hair samples by liquid chromatography-mass spectrometry (LC-MS). A 20 mg sample of hair was ground with 2 mL of saturated sodium carbonate solution using a high-efficiency hair grinder with 70 Hz oscillation for 2 min at 4 °C. After centrifuging, 1.5 mL of the supernatant was transferred and treated with SPME by direct immersion (DI-SPME). The target analytes extracted by fibre were desorbed and analysed using LC-MS. Under the optimum conditions, a recovery of 90.2%–95.8% was obtained for all analytes. The analytical method was linear for all analytes in the range from 0.2 to 10 ng/mg with the correlation coefficient ranging from 0.9985 to 0.9993. The detection limits for all analytes were estimated to be 0.067 ng/mg. The accuracy (mean relative error) was within ±6.9% and the precision (relative standard error) was less than 6.8%. The combination of high-speed grinding of hair and SPME had the advantages of being easy to perform, environment-friendly and high in detection sensitivity. The proposed method offered an alternative analytical approach for the sensitive detection of drugs in hair samples for forensic purposes.Key Points The SPME was involved for the determination of drugs in hair with LC-MS. The hair high-speed grinding combined with SPME was firstly developed. Good linearity, sensitivity, recovery and precision were achieved.